AirAsia’s Efforts in Maintaining Good Workplace Environment for its Employees During Covid-19 - Irdina, Irdina; Kee, Daisy Mui Hung; Reddy, Vasunthra; Izzati, Zafirah; Sri, Kamini; Perez, Manuela Granda; Restrepo, Camilo Alberto Perez; Lopez, Carolina Ardila; Das, Akash; Malhotra, Kunal; Pandey, Rudresh (AIBPM Publisher, 2020)
This study aims to examine the relationship between the workplace environment and employees’ satisfaction; to what extent can the workplace environment affect job satisfaction? The study used past research and interviewing an employee on job satisfaction and so was able to come up with reliable conclusions. The results showed a positive and strong correlation between workplace environment and job satisfaction. This study enhances the understanding of job satisfaction which can be used by managers to create a better workplace environment and boost employee performances.